Socio-economic values of wetland resources around Lake Manyara, Tanzania: assessment of environmental threats and local community awareness on environmental degradation and their effects - Nonga, HE; Mdegela, RH; Lie, E; Sandvik, M; Skaare, JU (Journal of Wetlands Ecology, 2011)
Understanding local people’s socio-economic values of wetlands and traditional mechanisms of managing natural resources forms the basis of conserving them. Wetlands have frequently been developed for short-term economic gains that destroy their ecological values and environmental services in the long term. A study was carried out to assess socio-economic values of the wetland resources, environmental threats around Lake Manyara and local community awareness on causes of environmental changes, degradation in the wetlands and their effects using 80 respondents. Field surveys, interviews, questionnaires and direct observation were used in data collection. It was found that local community was aware on the ecosystem services accrued from the wetlands which were unsustainably used. However, environmental degradation due to unsustainable agriculture, overgrazing, deforestation, urbanization and mining was rampant which had resulted to soil erosion, reduced water availability, wildlife mortality and frequent dry up of Lake Manyara and rivers. In order to protect the lake basin; controlled human activities, land use and water resources within the catchment are to be done in cooperation between the government departments, local authorities and the general local community around. Key words: Ecosystem services; rivers; Lake Manyara; wetland; agriculture DOI: 10.3126/jowe.v4i0.4153 Journal of Wetlands Ecology, (2010) Vol. 4, pp 83-101